2013
DOI: 10.1007/s13246-013-0180-6
|View full text |Cite
|
Sign up to set email alerts
|

Australian diagnostic reference levels for multi detector computed tomography

Abstract: The Australian Radiation Protection and Nuclear Safety Agency (ARPANSA) is undertaking web based surveys to obtain data to establish national diagnostic reference levels (DRLs) for diagnostic imaging. The first set of DRLs to be established are for multi detector computed tomography (MDCT). The survey samples MDCT dosimetry metrics: dose length product (DLP, mGy.cm) and volume computed tomography dose index (CTDIvol, mGy), for six common protocols/habitus: Head, Neck, Chest, AbdoPelvis, ChestAbdoPelvis and Lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…Figure 4 and Table 2 show that the post-intervention maximum DLP is some two times the minimum, whereas considerably larger values have been observed elsewhere. 12,15,16 For example, a recent study of CT doses in Ireland shows the same 75th percentile as that observed in this study and a very similar minimum DLP, but the maximum is 50% higher than that observed here, the ratio of minimum to maximum being approximately 3.5. Full paper: CT CAP doses in Scotland: has the DRL had its day?…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 4 and Table 2 show that the post-intervention maximum DLP is some two times the minimum, whereas considerably larger values have been observed elsewhere. 12,15,16 For example, a recent study of CT doses in Ireland shows the same 75th percentile as that observed in this study and a very similar minimum DLP, but the maximum is 50% higher than that observed here, the ratio of minimum to maximum being approximately 3.5. Full paper: CT CAP doses in Scotland: has the DRL had its day?…”
Section: Discussionsupporting
confidence: 85%
“…Data collected in the 2003 NRPB review 11 for CT CAP examinations and which provided the existing UK DRL of 940 mGy cm, using data from 36 multislice scanners, demonstrate such a distribution of data. Two recent publications that describe the dose distributions obtained in national data collections of CT data 12,15 -and which used sample sizes broadly similar to that used here-have shown distributions of CT dose data that are positively skewed and are not dissimilar in shape to those obtained in the 2003 review. This is most definitely not the case with the data collected in this study.…”
Section: Discussionmentioning
confidence: 77%
“…contrast, number of phases, technique factors, reconstruction method and dose modulation information). The details of the service have been described in a previous publication . As a quality improvement activity, this project was exempt from research ethics approval.…”
Section: Methodsmentioning
confidence: 99%
“…Since the first publication of the Australian NDRLs for adult MDCT in 2012, MDCT technologies have changed significantly and together with dose optimisation initiatives, this necessitated a review of the Australian NDRLs. In addition, the International Commission on Radiological Protection (ICRP) recommends that NDRLs should be reviewed at regular intervals (3–5 years) .…”
Section: Introductionmentioning
confidence: 99%
“…As part of this project, ARPANSA has hosted a database and internet data portal for the National Diagnostic Reference Level Service (NDRLS). 4 The NDRLS enables diagnostic radiology facilities to meet their obligations under the Code of Practice for Radiation in the Medical Applications of Ionizing Radiation (RPS 14, section 3.1.8) 5 to periodically compare patient doses with established DRLs. Imaging facilities enter technique, patient and radiation dose data for routine imaging protocols and receive a report comparing that dose data to the current national DRLs.…”
Section: Introductionmentioning
confidence: 99%